Developing a generic biosecurity risk assessment model for imports - Jamieson, L.E.; Woodberry, O.; McDonald, C.M.; Ormsby, M. (New Zealand Plant Protection, 2016)
Developing decision support models to evaluate biosecurity risks objectively helps decision makers manage the associated risks with importation of goods We report on the development of a prototype generic risk assessment model to determine the probability and consequences of a plant pest establishment and spread event for an infection point given the biosecurity risk organism arrives via various pathways The model has a number of submodels including entry pathway which models the ratio of infested units coming from any pathway supplying the infection point; establishment and spread which models the chance of an establishment and spread event occuring at an infection point; and consequences which models the consequences of any establishment or spread event occurring at the site Future research is planned to develop a generic input interface to generate a support tool to allow a user to investigate the impacts of alternative whatif scenarios and to test the model on realworld plant pest inputs